Community-Based Tele-Mentored Ultrasound for Urological Screening in Rural Primary Care - Afdal; Indra Jaya; Muhammad Teguh Hardiansyah; Muhammad Adan Yashar; Gatot Aji Prihartomo; Romy Deviandri; Sinta Chaira Maulanisa (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to assess the feasibility and impact of the community-based HHUS tele-mentoring program for urological screening in rural primary healthcare centers in Indonesia. A prospective quasi-experimental study was conducted from August to October 2025 at Pangkalan Baru Primary Health Center, Riau, Indonesia. Four general practitioners (GPs) underwent a one-day HHUS training session, followed by one month of tele-mentoring using the UroSono Mentor app, a telemedicine platform that supports both real-time video consultation and asynchronous image review, and one additional month of independent practice. Confidence, usability, feasibility, mentor responsiveness, patient satisfaction, and behavioral intention were assessed using structured questionnaires. Data were analyzed using the Friedman test (p < 0.05). Confidence scores improved significantly across all phases (p = 0.018), increasing from 2.06 (pre-training) to 4.37 (tele-mentoring) and 3.81 (independent practice). Training satisfaction was high (3.81 ± 0.19), with positive ratings for mentor responsiveness (4.44 ± 0.24) and usability (4.13 ± 0.14). Patient satisfaction averaged 4.49 ± 0.54. Of the 26 patients examined, 69.2% had normal findings, while 30.8% required referral. Community-based tele-mentored HHUS effectively enhanced GPs’ competence and confidence, achieving strong acceptance among both healthcare providers and patients. The UroSono Mentor model shows promise for scalable integration into rural urological screening programs.